El movimiento indígena no es aparentar, es luchar y seguir poniendo nuestra resistencia - Blanca Andrade (Les Cahiers ALHIM)
Blanca Andrade gives a testimony about the conditions of the Indigenous’s fights in the Páramo of Cauca, of their organizational ways, of the women’s involvement and about the current process of peace in Colombia.